Notary Deed in the Implementation of Local Government Asset Grants as an Effort to Transfer Regional Property - Dantes, Komang Febrinayanti; Utama, I Made Arya; Jayantiari, I Gusti Agung Mas Rwa; Bagiastra, I Nyoman (Journal of Ecohumanism, 2025)
The enactment Regulation of the Minister of Home Affairs Number 19 of 2016 concerning Guidelines for the Management of Regional Property changed arrangements regarding the procedure for implementing grants, which must be stated in a notarial deed. This study aims to analyze and examine the strength and legal certainty of notarial deeds related to the implementation of regional asset grants to transfer regional property which is carried out with the text of regional asset grant agreements or often called Regional Grant Agreement Text. This writing uses normative legal research methods. In grant activities, the utilization of regional property in the Province of Bali has resulted in a discrepancy between one regulation and another which is directly related to the administrative procedures for the implemented grant activities. From a dogmatic juridical point of view, a grant made in the form of a private deed must be considered empty and/or non-existent, so that the Regional Grant Agreement Text as a grant agreement text signed by the local government and the recipient of the grant has a weakness because it is a private deed so that it can be considered empty or nonexistent.